FAMILY NURSING CARE AT THE STAGE OF DEVELOPMENT OF SCHOOL-AGE CHILDREN: WITH COUNSELING INTERVENTION ON HAND WASHING - Thorik Rizky, Muhamad; Mardiyah, Siti; Windyastuti, Erlina (Universitas Kusuma Husada Surakarta, 2024)
Families with school-age children are a stage of family development starting from the first child being 6 years old and ending at the age of 12 years. At this stage, the family reaches its maximum number of members. School-aged children often do not pay attention to hand washing habits, especially in the school environment, so diseases such as diarrhea can spread. School-aged children need to be given knowledge about clean and healthy living behavior, one of which is by providing hand washing education. This case study aimed to determine the description of family nursing care at the developmental stage of school-aged children in the Gondangrejo Community Health Center area. This type of research is descriptive using a case study approach method. Data collection was carried out through interviews, observation, and documentation studies. The counseling uses the lecture method and poster media which contains about hand washing and the 6 steps for good and correct hand washing, accompanied by practicing how to wash hands well and correctly directly. The results of the activities showed that after the counseling was held, the level of knowledge and level of behavior increased, and children were able to understand the importance of washing their hands and implementing clean and healthy living behavior of washing their hands properly and correctly. Recommendation: Handwashing outreach intervention is important to increase knowledge and behavior of clean and healthy living in school-aged children.